The concept of evaluating the implementation of Honda classes in vocational schools using the CIPP Model - Mojibur Rohman; Eddy Sutadji (Jurnal Taman Vokasi, 2018)
Strategic collaboration between Vocational High Schools (SMK) and stakeholders can improve the quality of Vocational Schools. The quality improvement of SMK will undoubtedly be able to produce skilled human resources and be able to meet the needs of the workforce. One form of cooperation carried out by the Vocational School with the business world / industrial world is the Honda class program which is the cooperation of Vocational Schools with PT Astra Honda Motor (AHM). This evaluation concept aims to help research related to the effectiveness of Honda Class programs in Vocational Schools using the CIPP evaluation model (Context, Input, Process, and Product) developed by Stufflebeam. Through this evaluation model, researchers try to measure the effectiveness of Honda Class programs by analyzing the problems faced so that they can determine the strategic steps in resolving these problems.